N = 2 0 0 4 2 0 0 3 2 0 0 2 2 0 0 1 2 0 0 0 1 9 9 9 ⋯
What is the remainder when N is divided by 1000?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How could you think about that way?? Too genius! I only use Euler Totient function to do it.
Although @H.M. 유 's solution is faster, I would like to elaborate my solution, by using Euler Totient function here.
We have
N ≡ 4 2 0 0 3 2 0 0 2 . . . ( m o d 1 0 0 0 )
Because g c d ( 4 , 1 0 0 0 ) = 1 , so we separate it to
{ N ≡ 0 ( m o d 8 ) N ≡ 4 n 1 ϕ ( 1 2 5 ) + r 1 ( m o d 1 2 5 )
which n i and r i are positive integer.
So ϕ ( 1 2 5 ) = 1 0 0 , we get
N ≡ 4 1 0 0 n 1 + r 1 ( m o d 1 2 5 )
Then
2 0 0 3 2 0 0 2 2 0 0 1 . . . = 1 0 0 n 1 + r 1
r 1 ≡ 3 2 0 0 2 2 0 0 1 . . . ≡ 3 n 2 ϕ ( 1 0 0 ) + r 2 ≡ 3 4 0 n 2 + r 2 ( m o d 1 0 0 )
r 2 ≡ 2 0 0 2 2 0 0 1 2 0 0 0 . . . ≡ 2 2 0 0 1 2 0 0 0 . . . ( m o d 4 0 )
Again, since g c d ( 2 , 4 0 ) = 1 , separate it to
{ r 2 ≡ 0 ( m o d 8 ) r 2 ≡ 2 0 0 2 2 0 0 1 2 0 0 0 . . . ≡ 2 2 0 0 1 2 0 0 0 . . . ≡ 2 4 n 3 + r 3 ( m o d 5 )
Last step of this, we knew that ϕ ( 5 ) = 4 and 2 0 0 1 2 0 0 0 1 9 9 9 . . . ≡ 1 ( m o d 4 )
It leads to,
{ r 2 ≡ 0 ( m o d 8 ) r 2 ≡ 2 ( m o d 5 )
Then by Chinese Remainder Theorem , it gives us r 2 ≡ 3 2 ( m o d 4 0 )
Then r 1 ≡ 3 3 2 ≡ 8 1 8 ≡ ( − 1 9 ) 8 ≡ 1 9 8 ≡ 3 6 1 4 ≡ 6 1 4 ≡ 3 9 4 ≡ 1 5 2 1 2 ≡ 2 1 2 ≡ 4 4 1 ≡ 4 1 ( m o d 1 0 0 )
Recall that
{ N ≡ 0 ( m o d 8 ) N ≡ 4 n 1 ϕ ( 1 2 5 ) + r 1 ( m o d 1 2 5 )
By solving the second case of that, we have
{ N ≡ 0 ( m o d 8 ) N ≡ 7 9 ( m o d 1 2 5 )
Using Chinese Remainder Theorem again, we approach the answer
N ≡ 7 0 4 ( m o d 1 0 0 0 )
In my approach I have used the Carmichael's Lambda Function .
N = 2 0 0 4 2 0 0 3 2 0 0 2 2 0 0 1 2 0 0 0 1 9 9 9 ⋯
Now, since g c d ( 2 0 0 4 , 1 0 0 0 ) = 4 = 1 , we cannot apply the theory of Carmichael's Lambda Function, directly.
Note that N ≡ 0 m o d ( 8 ) so if we find N m o d ( 1 2 5 ) , then by Chinese remainder theorum we can get N m o d ( 1 0 0 0 ) .
Now, since g c d ( 2 0 0 4 , 1 2 5 ) = 1 we can use the Carmichael's Lambda Function.
λ ( 1 2 5 ) = 1 0 0
⇒ N ≡ 2 0 0 4 2 0 0 3 2 0 0 2 ⋯ m o d 1 0 0 m o d 1 2 5
Now again g c d ( 2 0 0 3 , 1 0 0 ) = 1 , so again we can use λ ( 1 0 0 ) = 2 0
⇒ N ≡ 2 0 0 4 2 0 0 3 2 0 0 2 2 0 0 1 ⋯ m o d ( 2 0 ) m o d ( 1 0 0 ) m o d ( 1 2 5 )
Again we see that g c d ( 2 0 0 2 , 2 0 ) = 2 = 1 ,so again we cannot apply the theory of Carmichael's Lambda Function.
Note that 2 0 0 2 2 0 0 1 2 0 0 0 ⋯ ≡ 0 m o d ( 4 ) so, if we find 2 0 0 2 2 0 0 1 ⋯ m o d ( 5 ) , then by Chinese Remainder theorum, we get 2 0 0 2 2 0 0 1 ⋯ m o d ( 2 0 ) ,Now 2 0 0 2 2 0 0 1 ⋯ ≡ 2 2 0 0 1 ⋯ m o d ( 5 )
2 0 0 2 2 0 0 1 ⋯ ≡ 2 2 0 0 1 ⋯ m o d ( 5 )
⇒ 2 0 0 2 2 0 0 1 ⋯ ≡ 2 2 0 0 1 ⋯ m o d ( 5 )
λ ( 5 ) = 4
⇒ 2 0 0 2 2 0 0 1 ⋯ ≡ 2 2 0 0 1 2 0 0 0 ⋯ m o d ( 4 ) m o d ( 5 )
Since 2 0 0 1 2 0 0 0 ⋯ ≡ 1 m o d ( 4 )
⇒ 2 0 0 2 2 0 0 1 ⋯ ≡ 2 m o d ( 5 )
So we have
2 0 0 2 2 0 0 1 2 0 0 0 ⋯ ≡ 0 m o d ( 4 )
≡ 2 m o d ( 5 )
So by Chinese Remainder theorum:
2 0 0 2 2 0 0 1 2 0 0 0 ⋯ ≡ 1 2 m o d ( 2 0 )
⇒ N ≡ 2 0 0 4 2 0 0 3 2 0 0 2 2 0 0 1 ⋯ m o d ( 2 0 ) m o d ( 1 0 0 ) m o d ( 1 2 5 ) ≡ 2 0 0 4 2 0 0 3 1 2 m o d ( 1 0 0 ) m o d ( 1 2 5 )
≡ 2 0 0 4 4 1 m o d ( 1 2 5 ) ≡ 7 9 m o d 1 2 5
Finally we have, N ≡ 7 9 m o d ( 1 2 5 ) and N ≡ 0 m o d ( 8 )
So By CRT we conclude N ≡ 7 0 4 m o d ( 1 0 0 0 )
Problem Loading...
Note Loading...
Set Loading...
We are going to prove some facts before we start figuring out the answer.
Fact 1.
Know that 2 1 1 = 2 0 4 8 and 2 3 = 8 .
Divide each of them by 4 0 and you'll see they have the same remainder.
So we can say that 2 1 1 ≡ 2 3 ( m o d 4 0 ) .
Then, for positive integer n and p ≥ 3 ,
2 8 n + p ≡ 2 p ( m o d 4 0 )
Fact 2.
Know that 3 5 = 2 4 3 ≡ − 7 ( m o d 5 0 ) .
Then you'll see 3 1 0 = ( 3 5 ) 2 ≡ 7 2 ≡ − 1 ( m o d 5 0 ) .
Therefore, for positive integer n ,
3 1 0 n ≡ ( − 1 ) n ( m o d 5 0 )
Fact 3.
Know that 7 6 2 = 5 7 7 6 ≡ 7 7 6 ( m o d 1 0 0 0 ) .
Then you'll see 5 7 6 2 = 5 0 0 2 + 2 × 5 0 0 × 7 6 + 7 6 2 ≡ 7 6 2 ≡ 7 7 6 ( m o d 1 0 0 0 ) .
5 7 6 3 = 5 7 6 2 × 5 7 6 ≡ 7 7 6 × 5 7 6 ≡ 7 0 0 × 5 0 0 + ( 1 0 0 0 + 2 0 0 ) × 7 6 + 7 6 2 ≡ 2 0 0 + 7 7 6 ≡ 9 7 6 ( m o d 1 0 0 0 )
Similarly,
5 7 6 4 ≡ 1 7 6 ( m o d 1 0 0 0 )
5 7 6 5 ≡ 3 7 6 ( m o d 1 0 0 0 ) .
Also, see that 3 7 6 2 = 3 0 0 × 3 0 0 + 2 × 3 0 0 × 7 6 + 7 6 2 ≡ 6 0 0 + 7 7 6 ≡ 3 7 6 ( m o d 1 0 0 0 ) .
Now, we can infer that 3 7 6 n ≡ 3 7 6 ( m o d 1 0 0 0 ) .
Therefore, 5 7 6 5 n + 4 = ( 5 7 6 5 ) n × 5 7 6 4 ≡ 3 7 6 n × 1 7 6 ≡ 3 7 6 × 1 7 6 ≡ 1 7 6 ( m o d 1 0 0 0 ) .
We can see that 4 1 0 = 2 2 0 = ( 2 1 0 ) 2 = 2 4 2 = 5 7 6 ( m o d 1 0 0 0 ) .
Therefore, for positive integer n ,
4 5 0 n + 4 0 ≡ 1 7 6 ( m o d 1 0 0 0 )
Now let's figure out the answer.
Firstly, note that 2 0 0 1 2 0 0 0 1 9 9 9 ⋯ ≡ 1 ( m o d 8 ) .
Then for a positive number k , using Fact 1 ,
2 0 0 2 2 0 0 1 2 0 0 0 ⋯ = 2 0 0 2 8 k + 1 ≡ 2 8 ( k − 1 ) + 9 ≡ 2 9 ≡ 3 2 ( m o d 4 0 ) .
.
Then for a positive number m , using Fact 2 ,
2 0 0 3 2 0 0 2 2 0 0 1 ⋯ ≡ 3 4 0 m + 3 2 ≡ ( 3 1 0 ) 4 m + 3 × 3 2 ≡ ( − 1 ) 4 m + 3 × 9 ≡ − 9 ≡ 4 1 ( m o d 5 0 ) .
.
Then, for a positive number n , using Fact 3 ,
2 0 0 4 2 0 0 3 2 0 0 2 ⋯ ≡ 4 5 0 n + 4 1 ≡ 4 5 0 n + 4 0 × 4 ≡ 1 7 6 × 4 ≡ 7 0 4 ( m o d 1 0 0 0 ) .
Therefore, N ≡ 7 0 4 ( m o d 1 0 0 0 ) .